Officiating speech 15th UiTM International Dental Student’s Scientific Symposium 2025 / Prof. Dr Haidzir Abd Manaf - Abd Manaf, Haidzir (2025)
First and foremost, I would like to congratulate the Faculty of Dentistry and the organising committee for their unwavering commitment and dedication in hosting this annual event – an event that has grown in both prominence and significance over the years.